2023
DOI: 10.1038/s41598-023-33148-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel visual illusion paradigm provides evidence for a general factor of illusion sensitivity and personality correlates

Abstract: Visual illusions are a gateway to understand how we construct our experience of reality. Unfortunately, important questions remain open, such as the hypothesis of a common factor underlying the sensitivity to different types of illusions, as well as of personality correlates of illusion sensitivity. In this study, we used a novel parametric framework for visual illusions to generate 10 different classic illusions (Delboeuf, Ebbinghaus, Rod and Frame, Vertical-Horizontal, Zöllner, White, Müller-Lyer, Ponzo, Pog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In fact, cognitive abilities often yield positive correlations, a concept known as Spearman's positive manifold (Ritchie, 2015). In keeping with the trend found in studies of cognition, Makowski et al (2023) have indeed found a general factor underlying perceptual illusion. Moreover, they claim this general susceptibility factor is positively related to positive personality traits (such as agreeableness) and negatively related to dark-triad personality traits.…”
Section: Individual Differences In Visual Illusions: Graphical and An...supporting
confidence: 87%
See 2 more Smart Citations
“…In fact, cognitive abilities often yield positive correlations, a concept known as Spearman's positive manifold (Ritchie, 2015). In keeping with the trend found in studies of cognition, Makowski et al (2023) have indeed found a general factor underlying perceptual illusion. Moreover, they claim this general susceptibility factor is positively related to positive personality traits (such as agreeableness) and negatively related to dark-triad personality traits.…”
Section: Individual Differences In Visual Illusions: Graphical and An...supporting
confidence: 87%
“…The first is that individual differences in visual illusions are at best weakly correlated (Cretenoud et al, 2019) and the proportion of variance accounted for any illusion on any other is surprisingly small. The second is that individual differences are related by a common factor which may even reflect personality differences (Makowski et al, 2023). We find support for both positions.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation